EFEKTIVITAS PROGRAM MOTEKAR (MOTIVATOR KETAHANAN KELUARGA) DALAM MENEKAN ANGKA PERCERAIAN DI KOTA BANJAR TAHUN 2021 - Riza Purnama; Mira Andriani (Jurnal Pemerintahan dan Politik, 2022)
ABSTRACT Motekar cadres (Family Resilience Motivators) were formed in 2014 by recruiting around 1,000 motekar cadres spread across villages/kelurahan in 27 regencies/cities in West Java, especially areas that have a relatively low level of family resilience, both vulnerable and characterized by The divorce rate is high, and that's what happened in the City of Banjar, it has been 7 years since the establishment of this Motekar program, but the population of Banjar City is the highest in West Java, at 3.74%. The writer uses descriptive qualitative research method in order to deepen the findings and analysis of the research. The theory used as a knife of analysis is the effectiveness of budiani. The results of the study found that first, the accuracy of the program had not run as expected because it turned out that the ratio of Motekar cadres was 1: 9,983, so it was not possible for this program to be on target as a whole. Second, in terms of program socialization, there were findings that the majority of the people of Banjar City did not know what the Motekar program was. Third, from the dimensions of the accuracy of the program and the socialization of the program that has not been fully implemented, that is the reason why the objectives of this program have not been achieved. Namely, one of its achievements is to reduce the divorce rate which is the estuary of vulnerable family problems. Although, this motekar program is an innovation from the West Java Provincial Government. It needs special attention from the Banjar City Government as a coach and user of energy from motekar cadres, so that the problems of vulnerable families that lead to divorce can be suppressed. Keywords : Effectiveness, Motekar, Divorce, Family Resilience  ABSTRAKKader Motekar (Motivator Ketahanan Keluarga) dibentuk pada tahun 2014 dengan merekrut sekitar 1.000 orang kader motekar yang  tersebar di Desa/Kelurahan di 27 Kabupaten/Kota di Jawa Barat, terutama daerah-daerah yang memiliki tingkat ketahanan keluarga yang relatif rendah, baik rentan ditandai dengan angka perceraian yang tinggi, dan itu yang terjadi di Kota Banjar, sudah 7 tahun sejak dibentuknya program motekar ini, namun angka penduduk Kota Banjar tertinggi di Jawa Barat, yakni diangka 3,74%. Metode penelitian kualitatif deskriptif penulis gunakan dalam agar memperdalam temuan dan analisis penelitian. Teori yang digunakan sebagai pisau analisis adalah efektivitas dari budiani. Hasil penelitian menemukan pertama, ketepatan program belum berjalan sesuai harapan karena ternyata rasio kader motekar 1: 9.983, sehingga tidak memungkin program ini tepat sasaran secara menyeluruh. Kedua, dari segi sosialisasi program, terdapat temuan bahwa masyarakat Kota Banjar mayoritas belum mengetahui apa itu program Motekar. Ketiga, dari dimensi ketepatan program dan sosialisasi program yang belum berjalan dengan sepenuhnya, itulah yang menyebabkan tujuan program ini belum tercapai. Yakni salahsatu capaiannya adalah menurunkan angka perceraian yang merupakan muara dari permasalaha keluarga rentan. Walaupun, program motekar ini adalah inovasi dari Pemerintah Provinsi Jawa Barat Perlu perhatian khusus dari Pemerintah Kota Banjar sebagai pembina dan pengguna tenaga dari kader motekar, sehingga permasalahan keluarga rentan yang berujung perceraian dapat ditekan. Kata Kunci : Efektivitas, Motekar, Perceraian, Ketahanan Keluarga